Preliminary evaluation of associated viruses in production systems of cape gooseberry, purple passion fruit, and rose - Cutler, Joseph; Langer, Juliane; Von Bargen, Susanne; Acosta-Losada, Orlando; Casierra-Posada, Fánor; Castañeda-Cárdenas, Adriana; Betancourt-Vásquez, Mónica; Cuellar, Wilmer; Arvydas-Stasiukynas, Eduardo; Altenbach, Denise (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
Plant viruses may pose a threat to crops in Colombia. To evaluate the potential risk of yield losses due to plant virus infection, a literature analysis followed by a first field study was carried out focusing on purple passion fruit (Passiflora edulis Sims), cape gooseberry (Physalis peruviana L.), and ornamental rose (Rosa sp.), which are important Colombian exports. Over the past three years, plant material was collected from 21 farms in Cundinamarca and Boyacá, Colombia, two regions that are in close proximity to El Dorado International Airport, the country’s largest air freight terminal. Plants were visually inspected and subsequently tested by bioassay and serological methods. Overall, in the samples investigated by the two diagnostic methods, plant viruses were detected. Detected viruses belong to the genus Poty-, Tobamo-, Nepo-, Ilar-, and Tospovirus. The extent of the distribution and occurrence of these viruses in each crop has to be determined in a representative field study. Such a monitoring program could be supported by a standardized farmer interview. The development of suitable plant virus diagnostic and managements tools is the focus of a cooperation project between German and Colombian universities, the Colombian Agricultural Institute (ICA), the Colombian Corporation of Agricultural Investigation (AGROSAVIA) and the International Center for Tropical Agriculture (CIAT).